Microbial Infection and Antibiotic Susceptibility of Diabetic Foot Ulcer in China: Literature Review - Du, Fang; Ma, Jing; Gong, Hongping; Bista, Raju; Zha, Panpan; Ren, Yan; Gao, Yun; Chen, Dawei; Ran, Xingwu; Wang, Chun (Frontiers in Endocrinology, 2022)
Objective: To investigate the microbial spectrum isolated from the foot ulcers among the diabetic patients in China, which was conducted to help the clinicians to choose optimal antibiotics empirically. Method: The PubMed, MEDLINE, Web of Science, China Biology Medicine (CBM), China National Knowledge Infrastructure (CNKI), WanFang, and VIP databases were searched for studies published from 2015 to 2019, that reported primary data on diabetic foot infection (DFI) and antibiotic susceptibility in China. Result: A total of 63 articles about DFI and antibiotic susceptibility test among the diabetic patients in China were included. There were 11483 patients with an average age of 60.2±10.1 years and mean course of 10.6±5.0 years during 2010 and 2019 covered most geographical regions of China. The prevalence of Gram-positive (GP) bacteria (43.4%) were lower than that of the Gram-negative (GN) (52.4%). The most prevalent pathogens isolated were Staphylococcus aureus (17.7%), Escherichia coli (10.9%), Pseudomonas aeruginosa (10.5%), Klebsiella pneumoniae (6.2%), Staphylococcus epidermidis (5.3%), Enterococcus faecalis (4.9%), and fungus (3.7%) in China. The prevalence of polymicrobial infection was 22.8%. GP bacteria were sensitive to linezolid, vancomycin, and teicoplanin. More than 50% GN bacteria were resistant to the third-generation cephalosporins, while the resistance rates of piperacillin/tazobactam, amikacin, meropenem, and imipenem were relatively low. Among 6017 strains of the isolated organisms, 20% were multi-drug resistance (MDR) and Staphylococcus aureus (30.4%) was the most predominant MDR bacteria, followed by extended-spectrum β-lactamase (ESBL) (19.1%). Conclusion: The microbial infection on the foot ulcers among the diabetic patients in China is diverse. Microbial spectrum is different in different geographic regions and Staphylococcus aureus is the predominant bacteria. Polymicrobial and MDR bacterial infections on the foot ulcers are common. This study could be valuable in guiding the empirical use of antibiotics for the diabetic foot infections.